Food Safety Compliance for Kansas Food Operations and Consumers: Analyzing trends, Developing educational materials, and Improving communication - Barnes, Cheryl (My University, 2022)
Food safety has become a common subject in the news and in our everyday lives. Recalls documented from the United States Department of Agriculture (USDA), restaurant outbreaks, and people becoming severely ill from foodborne illnesses are becoming a common occurrence. Every year unsafe food causes an estimated 600 million cases of foodborne illness worldwide and an 420,000 deaths.1 It’s an important public health issue that has many layers and complexes within it. There are so many hands that touch food from farm to plate. It’s everyone’s responsibility to be educated on food safety and to apply those skills and knowledge with each food that is touched. The increase of trade, globalization, and consumers eating food outside of the home has made for a longer and more complex food supply chain. It's critical that there is collaboration between the government, producers of food, and consumers to strengthen the food safety system.2 One of the Healthy People 2030 goals is to “Improve food handling practices,” which includes reducing infections and outbreaks caused by pathogens in food, and increasing safe food handling practices.3 Common violations that food operations are cited for include food contact surfaces not being properly cleaned or sanitized; toxic substances not being properly identified, stored, or used; physical facilities not being installed, maintained, and cleaned; not properly date marking; and not having adequate handwashing sinks supplied and accessible.4 For my integrated learning experience, I worked with the Kansas Department of Agriculture (KDA) and we aimed to increase education on these topics. I helped create and reform educational materials for operations that are overseen by KDA with the Kansas Food Code 2012 which is based on the US Public Health Service (PHS) 2009 FDA Model Food Code. It has also become increasingly important that consumers are educated in cooking safe food in their home and understanding food safety while they are dining out. Connecting consumers with updated and new information can help reduce the amount of foodborne illnesses caused at home and from eating out. This is why I also assisted Kansas State Research and Extension (KSRE) staff on 1) creating new educational materials and updating ones for consumers, and 2) identifying gaps in publications available within their online bookstore. This paper is a detailed summary of my experience in the field.
Keywords: food safety; food establishments; restaurants; consumers; educational materials; food code